INDIANNESS AND KANNADATVA IN THE EYES OF KUVEMPU AND DR. SIDDHALINGAYYA - Bharathi Devi .P (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Nationalism acted as a unifying factor in the Indian independence movement during British rule. However, nationalism includes a policy of separating us from other people. Our writers, intellectuals, and activists have been influenced by this. Numerous works of literature are inspired with a sense of nationalism. However, the renowned Kannada poets Kuvempu and Dr. Siddalingaiah have argued that the inclusion principle is different from the idea of division. This article makes an effort to comprehend this.